Comparacion de la dinamica del crecimiento de los pomelos "Frost marsh" y Marsh jabarito" en fase de vivero - Rodriguez, N.=700 1 Alvarez, M.
(Es, En)
Ilus., 10 ref.
Keywords: CITRUS GRANDIS; CRECIMIENTO; INJERTO; CITRUS AURANTIUM; VIVEROS; CUBA; POMELO